The Edinburgh human metabolic network reconstruction and its functional analysis - Hongwu Ma; Anatoly Sorokin; Alexander Mazein; Alex Selkov; Evgeni Selkov; Oleg Demin; Igor Goryanin (Molecular Systems Biology)
Abstract A better understanding of human metabolism and its relationship with diseases is an important task in human systems biology studies. In this paper, we present a high‐quality human metabolic network manually reconstructed by integrating genome annotation information from different databases and metabolic reaction information from literature. The network contains nearly 3000 metabolic reactions, which were reorganized into about 70 human‐specific metabolic pathways according to their functional relationships. By analysis of the functional connectivity of the metabolites in the network, the bow‐tie structure, which was found previously by structure analysis, is reconfirmed. Furthermore, the distribution of the disease related genes in the network suggests that the IN (substrates) subset of the bow‐tie structure has more flexibility than other parts.